Comparison of Secondary Metabolite Extraction Methods in Hamelia patens Jacq. and Their Inhibitory Effect on Fusarium oxysporum f. sp. radicis-lycopersici - Daniel Jafet Valle Ortiz; Dolores Guadalupe Aguila Muñoz; María del Carmen Cruz López; Diana Verónica Cortés Espinosa; Martha Rosales Castro; Fabiola Eloísa Jiménez Montejo (Metabolites)
Background: Hamelia patens Jacq. (HP) is widely recognized in traditional medicine for its antimicrobial properties, which are attributed to secondary metabolites such as phenolic compounds, alkaloids, and terpenes. Fusarium oxysporum f. sp. radicis-lycopersici (Fo), a phytopathogenic fungus affecting economically important crops, is managed with fungicides like benzimidazoles and azoles. Excessive use of these compounds has led to resistance and environmental contamination, highlighting the need for sustainable alternatives. This study aimed to optimize the extraction of secondary metabolites from HP leaves and flowers, evaluate their antifungal activity, and assess the impact of extraction methods and plant parts on chemical composition and efficacy. Methods: Three extraction methods were employed: consecutive maceration (CM) using solvents of ascending polarity; total maceration (TM), which is a single-step methanol-based method; and ultrasound-assisted maceration (UAM) employing ultrasonic waves with methanol. Extracts were characterized by quantifying total phenols (TP), condensed tannins (TC), flavonoids (Fl), alkaloids (TA), sterols (TS), and saponins (S) using colorimetric assays and UPLC-MS. Multivariate analyses, including PCA, PLS-DA, OPLS-DA, and Pearson correlation, evaluated the relationships between the chemical profiles and antifungal activity. Results: Leaf extracts exhibited higher flavonoid and tannin contents than flower extracts. CMML showed the highest antifungal activity (IC50 3.7% w/v), which was associated with elevated levels of these compounds. Significant correlations linked antifungal activity with rutin (HP21) and kaempferol-3-O-β-rutinoside (HP29). Conclusions: Methanolic extracts of HP exhibited significant antifungal activity against Fo. These findings highlight the importance of optimizing extraction methods and selecting specific plant parts to enhance bioactive compound efficacy, offering a sustainable approach to pathogen management.